The Impact of CSR and Profitability on Firm Value: Evidence From IDX-Listed Mining Companies (2020-2023) - Rahayu, Peby; Yanuar, Tendi; Komara, Acep (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: This study aims to analyze the effect of CSR and profitability on firm value in the mining sub-sector listed on the IDX for the period 2020-2023. Design/methodology/approach: The research method used a quantitative approach with multiple linear regression analysis on a sample of 25 companies. Firm value as the dependent variable was measured using PBV, while the independent variables included CSR, which was measured using the CSR Disclosure Index in accordance with the 2021 GRI Standards, and profitability, which was measured using ROA. Findings: The findings explain that CSR does not have a significant impact on company value, profitability has a negative and significant impact on company value, and company size as a control variable also has a negative impact on company value. Research limitations/implications: The limitations of this study are that it only covers companies operating in the mining sector listed on the Indonesia Stock Exchange (IDX) and only uses two independent variables and one control variable, namely CSR, profitability, and company size. Practical implications: This study shows that these two factors do not always have a positive impact. These results highlight the importance of market perceptions of sustainability and corporate governance in promoting sustainable economic development Originality/value: This study confirms that economic growth and development in Indonesia's mining sector is not only determined by corporate profits and size, but also by market perceptions of sustainability and corporate governance. Therefore, concrete incentives are needed for companies to implement CSR, investment assessments that consider sustainability aspects, and policies that promote efficiency and corporate governance in large companies. Paper type: Research paper